Staff perspectives on the relationship between knowledge management and social capital with organizational health in selected educational hospitals in Tehran - Aidin Aryankhesal; Mahdi Hasani; Noureddin Niknam; Mehdi Safari; Asaad Ranaei; Ehsan Allah Kalteh (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Knowledge management enhances efficiency, empowers employees, and enhances organizational health. Social capital provides a good basis for more productive human resources, and training hospitals also play a key role in the health-care system. The purpose of this study was to determine the relationship between knowledge management and social capital with organizational health in selected educational hospitals of Tehran in 2018. METHODS: This analytical cross-sectional study was performed on 310 medical staff of hospitals using proportional sampling method. The data gathering tools consisted of three standard questionnaires of knowledge management, social capital, and organizational health. Data were analyzed using descriptive and inferential statistics using SPSS version 22 software. RESULTS: Most participants in this study were male (8/66%) and in the age group 31-36 years. The mean of knowledge management and organizational health were 3.43 and 3.49, respectively. There is a significant direct relationship between knowledge management components and organizational health. Moreover, there is a significant but weak direct relationship between knowledge management and social capital with organizational health dimensions (P ≤ 0.05). CONCLUSION: Considering the relationship between knowledge management and social capital with organizational health, enhancing the level of organizational health can help to improve the dimensions of knowledge management and social capital. It is suggested that hospital managers, using knowledge management and social capital components, enhance organizational health so that the hospital is more prepared to adapt to the complexities and changes in the market providing services.